ANALISIS TINGKAT RESIKO DAMPAK GEMPABUMI DI KABUPATEN CILACAP MENGGUNAKAN METODE DSHA DAN DATA MIKROTREMOR - Kukuh Dialosa; Rustadi Rustadi; Bagus Sapto Mulyatno; Cecep Sulaeman (Engineering Faculty Universitas Lampung, 2018)
Soil mechanical research has been done in Cilacap Regency using DSHA method and microtremor data. This study aims to analyze the local land response to earthquakes based on the dominant frequency parameters (f0), amplification factor (A0), wave velocity VS30 and seismic hazard analysis through deterministic approach. This research uses 193 microtremor measurement points using a short period TDS-303 type (3 component) seismometer. Microtremor data were analyzed using the Horizontal to Vertical Spectral Ratio (HVSR) method in geopsy software. DSHA analysis refers to the source of the Lembang Fault earthquake and Java Subduction zone for deterministic calculations. Based on the analysis of HVSR method, Cilacap Regency is located on land type 1 (frequency 0-1.33 Hz) and soil type 2 (frequency 1,33-5 Hz) according to Kanai Classification (1983), dominated amplification value 1,104 to 8,171 times, then Dominated by soil class E (VS30 value 183 m / s) and soil class D (183 m / s VS30 366 m / s) according to NEHRP Classification (2000). This indicates that Cilacap Regency has high vulnerability to earthquake disaster. Based on the estimated value of PGA calculation method of DSHA, from the calculation of earthquake source Subduction obtained Java PGA bedrock 0,045 g - 0,0671 g and PGA surface rock 0,1926 g - 0,4855 g and calculation of Lembang Fault obtained PGA bedrock 0, 09 g - 0.025 g and PGA surface rocks 0.017 g - 0.089 g. Based on risk map analysis (combination of dominant frequency analysis, amplification, susceptibility factor and ability factor), the highest risk areas are Kec. Adipala, Kasugihan, Binangun, Nusawungun, Cil. Middle, Cil. South, Cil. North, allegedly the soil layer constituent area is a layer of thick and soft sediments. While the low risk of Kec. Majenang and Dayeuh Luhur.